The implications and applications of nanotechnology in dentistry: A review - Rawan N. AlKahtani (Elsevier, 2018)
The emerging science of nanotechnology, especially within the dental and medical fields, sparked a research interest in their potential applications and benefits in comparison to conventional materials used. Therefore, a better understanding of the science behind nanotechnology is essential to appreciate how these materials can be utilised in our daily practice. The present paper will help the reader understand nanoscience, and the benefits and limitations of nanotechnology by addressing its ethical, social, and health implications. Additionally, nano-applications in dental diagnostics, dental prevention, and in dental materials will be addressed, with examples of commercially available products and evidence on their clinical performance. Keywords: Nanodentistry, Nanotechnology, Nanomaterials